1991
DOI: 10.1002/hep.1840140212
|View full text |Cite
|
Sign up to set email alerts
|

Graft vs. host disease after liver transplantation in humans: A report of four cases

Abstract: Four cases of patients in whom graft vs. host disease developed after liver transplantation are described. The clinical course of each patient was similar with fever, pancytopenia, diarrhea and a skin rash developing 1 or 2 mo after liver transplantation. The clinical diagnosis was made from skin or colon biopsy specimens. Liver dysfunction did not occur in the patients at the time of diagnosis. Extrahepatic donor DNA was identified in the three patients it was tested for. Three patients died from the complica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0

Year Published

1993
1993
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(35 citation statements)
references
References 13 publications
0
35
0
Order By: Relevance
“…In 61 cases (60.4%), sepsis was documented as cause of death. The causative organism was reported in 25 cases (41%); invasive aspergillosis was noted in 9 cases 1, 9, 1217 (36%), disseminated candidiasis in 7 (28%) (3 albicans , 1 kruseii , 1 glabrata and 2 unspecified species) 1, 9, 18, 19 , enterococci in 7 (28%) 1, 2023 and Enterobacter in 2 (8%) 1, 24 .…”
Section: Resultsmentioning
confidence: 99%
“…In 61 cases (60.4%), sepsis was documented as cause of death. The causative organism was reported in 25 cases (41%); invasive aspergillosis was noted in 9 cases 1, 9, 1217 (36%), disseminated candidiasis in 7 (28%) (3 albicans , 1 kruseii , 1 glabrata and 2 unspecified species) 1, 9, 18, 19 , enterococci in 7 (28%) 1, 2023 and Enterobacter in 2 (8%) 1, 24 .…”
Section: Resultsmentioning
confidence: 99%
“…6 By contrast, GvHD was not seen among 31 liver transplant patients investigated for diarrhoea at a Scottish transplant centre. 3 Roberts et al 7 reported four cases of colorectal GvHD among a non-selected cohort of 164 liver allograft recipients, but admitted themselves that this was an unexpectedly high incidence. The most common causes of diarrhoea in liver transplant recipients have been recorded in one case series to be (in order of decreasing frequency) Clostridium difficile infection, drugs, cytomegalovirus (CMV) infection, and inflammatory bowel disease; 3 and by others to be CMV and C. difficile infection and mycophenolate mofetil (MMF) toxicity, followed by other drugs and then inflammatory bowel disease.…”
Section: Spectrum Of Diseasesmentioning
confidence: 99%
“…With human liver transplantation, preoccupation with rejection obscured the fact until recently that the GVH reaction, which is an incipient process and a requisite for sustained engraftment in every case, can evolve to serious or fatal syndromes (124)(125)(126)(127)(128)(129)(130) in the early postoperative period. Clinically significant GVHD is observed in our liver program in approximately 5% of cases, manifesting as dermatitis.…”
Section: Failure Of Mixed Chimerismmentioning
confidence: 99%